PASAR UANG DITINJAU DARI SOSIOLOGI EKONOMI - H. Syahrul, H. Syahrul (DIKTUM: Jurnal Syariah dan Hukum, 2013)
Money market is a market where securities are traded short-term, while the foreign exchange market is a market where securities are traded in a currency with another currency involved. Money Market Rates in Conventional usually expressed in a percentage that represents revenue associated with the use of money for a certain period of time. Interbank Money Market Sharia is a short-term investment activity in dollars between market participants based on the principle of Mudaraba, which is an agreement between the investor funds and fund managers to conduct business for profit, and the profit will be distributed to both parties at a ratio teiah agreed upon in advance. Letter of Bank Indonesia Wadiah (SWBI) has diganukan with instruments called Deposit Bank Indonesia Sharia abbreviated FASBIS. FASBIS is the deposit facility provided by Bank Indonesia to Bank for placing funds in Bank Indonesia Sharia in order jucilities standing.